Pengaruh Gaya Belajar dan Kemandirian Belajar terhadap Hasil Belajar Matematika Siswa di Kelas VIII SMP YPK Kotaraja - Wa Ode Chelsi Nur; Happy Lumbantobing; Rian Efendi; Raoda Ismail; Dewi Kristika Findya Ning Tyas; Agnes Teresa Panjaitan; Mayor Manurung; Elieser Kulimbang (EDUPEDIA PUBLISHER, 2026)
Purpose: This study examined the individual and joint effects among Grade 7 students at SMP YPK Kotaraja, Papua, Indonesia. Methodology: A quantitative ex post facto design was employed with 129 students selected proportionally from a population of 187. Data were obtained through validated questionnaires measuring visual, auditory, and kinesthetic learning styles and self-regulated learning, together with official mathematics grades. Simple and multiple linear regression analyses were used after the data met assumptions. Findings: The results showed that learning styles and self-regulated learning each significantly predicted mathematics learning outcomes, with self-regulated learning exerting the stronger contribution. When examined simultaneously, both variables explained 82.3% of the variance in mathematics learning outcomes. The visual learning style predominated, representing 51.94% of the sample. These findings indicate that students’ capacity to plan, monitor, regulate, and evaluate their learning is more strongly associated with mathematics achievement than learning preferences alone. Significance: Learning styles remain relevant for designing responsive instruction, but instructional strategies should prioritize learner autonomy, responsibility, and active engagement. Overall, strengthening self-regulated learning while accommodating diverse learning styles may support improved mathematics learning outcomes and more responsive mathematics instruction in underrepresented educational contexts.